Comparison of stigmatizing views towards COVID-19 and mental disorders among adolescent and young adult students in China - Zhang, Tian-Ming; Zhang, Xin-Feng; Meng, Xian-Dong; Huang, Yi; Zhang, Wei; Gong, Hui-Hui; Chan, Sherry Kit Wa; Chen, Xiao-Chuan; Gao, Ru; Lewis-Fernández, Roberto; Fan, Yuan-Yuan; Liu, Chang-Cheng; et al. (Frontiers in Psychiatry, 2023)
Objective Infectious diseases including COVID-19 and mental disorders are two of the most common health conditions associated with stigma. However, the comparative stigma of these two conditions has received less attention in research. This study aimed to compare the prevalence of stigmatizing views toward people with COVID-19 and mental disorders and the factors associated with these views, among a large sample of adolescent and young adult students in China. Methods A total of 9,749 adolescents and young adults aged 15–24 years completed a survey on stigmatizing attitudes toward COVID-19 and mental disorders, as well as mental health-related factors, including general mental health status and symptoms of depression, anxiety, insomnia, and post-traumatic stress disorder (PTSD). Multivariable linear regression analyses were conducted to identify factors associated with stigmatizing views. Findings The prevalence of COVID-19 and mental disorders-related stigma was 17.2% and 40.7%, respectively. COVID-19-related stigma scores were significantly higher among male students (β = 0.025, p < 0.05), those without quarantine experience (β = 0.035, p < 0.001), those with lower educational level (p < 0.001), those with lower family income (p < 0.01), and those with higher PTSD symptoms (β = 0.045, p < 0.05). Mental disorder-related stigma scores were significantly higher among individuals with average and lower-than-average levels of family income (p < 0.01), depression symptoms (β = 0.056, p < 0.001), anxiety symptoms (β = 0.051, p < 0.001), and mental health problems (β = 0.027, p < 0.05). Conclusion The stigma of mental disorders is higher in the youth population than the stigma of COVID-19. Factors associated with stigmatizing attitudes toward people with COVID-19 and mental disorders varied across the youth. Stigma-reduction interventions among the youth should be targeted specifically to COVID-19 or mental disorders conditions.